Investigating predictors contributing to the expression of schizotypy during the COVID-19 pandemic. (June 2022) - Toh, Wei Lin; Sumner, Philip J.; Meyer, Denny; Neill, Erica; Phillipou, Andrea; Tan, Eric J.; Van Rheenen, Tamsyn E.; Rossell, Susan L.
Abstract: The coronavirus (COVID-19) pandemic has caused major disruptions to social and other forms of functioning, which may influence schizotypy expression. The current study aimed to explore possible distal and proximal predictors contributing to schizotypy in a sample of the Australian general population during the COVID-19 pandemic. The COvid-19 and you: mentaL heaLth in AusTralia now survEy (COLLATE) project is an online mental health study aimed at tracking key mental health indicators over the progression of the pandemic. Adults residing in Australia were invited to take part using non-discriminative snowball sampling. Demographic-clinical information was collected for 850 participants in either October 2020 or January 2021. To assess schizotypy facets, the Launay-Slade Hallucinations Scale-Extended (LSHS-E) and Peters Delusions Inventory (PDI-21) were used to measure hallucination and delusion proneness respectively. Generalised linear models (with gamma and negative binomial distributions) were employed. Age, negative emotions and loneliness significantly contributed to both hallucination and delusion proneness; gender, education and religiosity also significantly contributed to delusion proneness, in the final regression models. Our study corroborated the specific contribution of loneliness, amongst other factors, in the prediction of schizotypy facets. Tackling loneliness represents a public health challenge that needs to be urgently addressed, especially in the face of the ongoing COVID-19 pandemic.